Pendidikan Kemanusiaan dalam Perspektif Hadis Nabi: Analisis Tahlili terhadap Nilai Solidaritas Umat Islam atas Krisis Sudan dan Palestina - Eka Susanti; Hairul Hudaya (CV. ITTC INDONESIA, 2025)
This study aims to analyze the hadiths of the Prophet Muhammad (peace be upon him) related to Muslim solidarity in responding to humanitarian crises in Sudan and Palestine. The prolonged crises in both regions require Muslim engagement that goes beyond emotional empathy and is grounded in the normative values of Islamic teachings. This research employs a qualitative approach using the tahlili method, which involves an in-depth analysis of hadiths through the examination of their chains of transmission (isnad), textual content (matn), historical context (asbāb al-wurūd), and substantive interpretation. The findings show that hadiths concerning ukhuwah Islamiyah (Islamic brotherhood), mutual assistance, empathy, and social responsibility have strong relevance in fostering collective awareness among Muslims regarding the suffering of their fellow believers. From the perspective of hadith, solidarity is not merely symbolic or rhetorical, but necessitates concrete, sustained, and well-organized actions oriented toward the realization of public welfare (maslahah). This study is expected to enrich thematic hadith studies and provide a conceptual contribution to strengthening Muslim humanitarian solidarity in addressing contemporary global crises.